2002
DOI: 10.1124/jpet.300.2.487
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fiduxosin, an Antagonist Selective for α1A- and α1D-Adrenoceptors, on Intraurethral and Arterial Pressure Responses in Conscious Dogs

Abstract: Fiduxosin is an ␣ 1 -adrenoceptor antagonist with higher affinity for ␣ 1A -adrenoceptors and for ␣ 1D -adrenoceptors than for ␣ 1B -adrenoceptors. Our hypothesis is that such a compound with higher affinity for subtypes implicated in the control of lower urinary tract function and lower affinity for a subtype implicated in the control of arterial pressure could result in a superior clinical profile for the treatment of lower urinary tract symptoms suggestive of benign prostatic obstruction. The purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Most compound dosages were adopted from literature. The dosages were CGS-15943 1mg/kg (24), 8-(3-chlorostyryl) caffeine 5 mg/kg (25), fluspirilene 1 mg/kg (26), fiduxosin hydrochloride 3 mg/kg (27), fluphenazin dihydrochloride 3 mg/kg (28), SB 228357 5 mg/kg (29), PQ 401 50 mg/kg (30), DMCM hydrochloride 3 mg/kg (31). PRL-3 inhibitor I has not been studied in vivo previously, 10 mg/kg was used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Most compound dosages were adopted from literature. The dosages were CGS-15943 1mg/kg (24), 8-(3-chlorostyryl) caffeine 5 mg/kg (25), fluspirilene 1 mg/kg (26), fiduxosin hydrochloride 3 mg/kg (27), fluphenazin dihydrochloride 3 mg/kg (28), SB 228357 5 mg/kg (29), PQ 401 50 mg/kg (30), DMCM hydrochloride 3 mg/kg (31). PRL-3 inhibitor I has not been studied in vivo previously, 10 mg/kg was used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…However, the contribution of the prostate appears to dominate because phenylephrine‐induced IUP elevations were about 80% smaller in prostate‐ablated male, castrated male or female as compared to prostate‐intact rats (Akiyama et al ., 1999). The systemic administration of α 1 ‐adrenoceptor agonists such as noradrenaline, adrenaline or phenylephrine has been shown to increase IUP in anaesthetized rats (Guilmard et al ., 1996; Martin et al ., 1997; Akiyama et al ., 1999), anaesthetized cats (Lefevre‐Borg et al ., 1993) and anaesthetized dogs (Breslin et al ., 1993; Kenny et al ., 1994; 1996; Testa et al ., 1997; Witte et al ., 1997; 2002; Pulito et al ., 2000; Eltze et al ., 2001) and conscious dogs (Brune et al ., 2002). Similar IUP elevations have also been produced by the systemic administration of α 1A ‐selective agonists such as A 61603 (Knepper et al ., 1995).…”
Section: Prostatementioning
confidence: 99%
“…Similar IUP elevations have also been produced by the systemic administration of α 1A ‐selective agonists such as A 61603 (Knepper et al ., 1995). Agonist‐induced IUP elevations were inhibited by various α 1 ‐adrenoceptor antagonists, including the clinically used alfuzosin (Lefevre‐Borg et al ., 1993; Kenny et al ., 1994; Guilmard et al ., 1996; Martin et al ., 1997; Testa et al ., 1997; Akiyama et al ., 1999), doxazosin (Kenny et al ., 1994; 1996; Martin et al ., 1997; Witte et al ., 2002), tamsulosin (Breslin et al ., 1993; Kenny et al ., 1994; 1996; Martin et al ., 1997; Testa et al ., 1997; Akiyama et al ., 1999; Pulito et al ., 2000; Brune et al ., 2002; Witte et al ., 2002) and terazosin (Breslin et al ., 1993; Kenny et al ., 1994; Martin et al ., 1997; Testa et al ., 1997; Witte et al ., 1997; 2002; Akiyama et al ., 1999; Brune et al ., 2002). Similar inhibition was also obtained when IUP elevations had been induced by stimulation of the hypogastric nerves (Lefevre‐Borg et al ., 1993; Leonardi et al ., 1997; Sato et al ., 2001), indicating its physiological relevance.…”
Section: Prostatementioning
confidence: 99%
“…Among the 1300 compounds screened here, we identified fiduxosin hydrochloride and flunarizine dihydrochloride as anti-HCV agents. Fiduxosin is known as an alpha1-adrenoceptor antagonist (39). Previous screening of a whole-genome siRNA library has shown that knockdown of alpha-1 adrenoceptor A, B, or D expression significantly reduces the replication of the genotype 1b subgenomic replicon (44), suggesting that alpha-1 adrenoceptors participate in the replication of HCV.…”
Section: Discussionmentioning
confidence: 99%
“…6b). Although fiduxosin and flunarizine are known to be antagonists of alpha-1 adrenoceptor (39) and T-type calcium ion channels (40), respectively, the mechanisms by which they inhibit HCV propagation are not known. These results indicate that the Huh7OK1/TG-Luc cell line is applicable for a reliable cell-based assay for high-throughput screening of anti-HCV drugs.…”
Section: Application Of Huh7ok1/tg-luc Cells For Screening Of Anti-hcmentioning
confidence: 99%